Can Dominant Runoff Generation Mechanisms Be Disentangled Through Hypothesis Testing? Insights From Integrated Hydrological‐Hydrodynamic Modeling - Pasquale Perrini; Vito Iacobellis; Andrea Gioia; Luis Cea; Hubert H. G. Savenije; Fabrizio Fenicia (Water Resources Research)
Abstract Identifying flood‐inducing processes remains a challenge in catchment hydrology due to the complex runoff dynamics, particularly in semi‐arid regions where surface and subsurface mechanisms alternatively drive streamflow across seasons. Tracer data can help identify hydrograph sources, but they are often unavailable or lack sufficient temporal resolution. To aid process identification at the event‐scale, we developed an integrated hydrological‐hydrodynamic framework and compared multiple model hypotheses informed by hydrological signatures. We systematically tested these hypotheses through falsification, meta‐evaluation, spatial validation, and posterior diagnostics, using the semi‐arid Salsola nested catchment in southern Italy as case study. While all model structures performed well on common calibration metrics, differences emerged in spatial transferability tests and alternative diagnostic assessments. Some models, despite strong performance, exhibited inconsistent representations of internal runoff mechanisms, indicating that they achieved good results for the wrong reasons. Furthermore, the choice of routing schemes significantly influenced high‐peak estimations and overall model performance, particularly when Horton‐type overland flow was considered. This underscores the need to treat routing methods as a key component in event‐scale modeling. Our findings reveal that during consecutive storm events in the study catchment, surface processes dominate the initial stages, whereas subsurface processes become more influential in later events, providing valuable insights that may be applicable to similar semi‐arid regions. Overall, we emphasize the importance of hypothesis testing in runoff process identification, which can compensate for the absence of hydrochemical data for hydrograph separation. Additionally, our results highlight the value of a landscape‐based modeling approach for distinguishing alternative runoff generation processes.